2010
DOI: 10.1007/s00114-010-0670-2
|View full text |Cite|
|
Sign up to set email alerts
|

Coping with chaos: unpredictable food supplies intensify torpor use in an arid-zone marsupial, the fat-tailed dunnart (Sminthopsis crassicaudata)

Abstract: , B. M. (2010). Coping with chaos: unpredictable food supplies intensify torpor use in an arid-zone marsupial, the fat-tailed dunnart (Sminthopsis crassicaudata). Naturwissenschaften, 97 (6), 601-605.Coping with chaos: unpredictable food supplies intensify torpor use in an arid-zone marsupial, the fat-tailed dunnart (Sminthopsis crassicaudata) AbstractThe severity, duration and amplitude of extreme weather events are forecast to intensify with current climate trends, over both long (e.g. seasonal) and short (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 25 publications
(20 reference statements)
1
33
0
Order By: Relevance
“…This framework suggests that periods of variable food intake due to variation in food abundance or interruptions in foraging due to increased 'risk' (such as predation or inclement weather) prompt individuals to regulate their body mass and energy usage (Bednekoff and Krebs, 1995;Witter et al, 1995; Cuthill et al, 2000). In birds and mammals, temporal variability in food availability is associated with fattening (Bednekoff and Krebs, 1995), an increase in daily torpor (Munn et al, 2010), increased or stabilized body mass (Witter et al, 1995; Cuthill et al, 2000) and less behavioral activity (Dall and Witter, 1998). These observations are consistent with the adaptive regulation hypothesis (Witter et al, 1995;Fauchald et al, 2004), which describes how animals coping with unpredictable food availability aim to decrease energetic expenditure and attenuate physiology that depletes energy reserves such as CORT secretion, thus promoting energy conservation, which conserves (or even increases) body mass.…”
Section: Discussionmentioning
confidence: 99%
“…This framework suggests that periods of variable food intake due to variation in food abundance or interruptions in foraging due to increased 'risk' (such as predation or inclement weather) prompt individuals to regulate their body mass and energy usage (Bednekoff and Krebs, 1995;Witter et al, 1995; Cuthill et al, 2000). In birds and mammals, temporal variability in food availability is associated with fattening (Bednekoff and Krebs, 1995), an increase in daily torpor (Munn et al, 2010), increased or stabilized body mass (Witter et al, 1995; Cuthill et al, 2000) and less behavioral activity (Dall and Witter, 1998). These observations are consistent with the adaptive regulation hypothesis (Witter et al, 1995;Fauchald et al, 2004), which describes how animals coping with unpredictable food availability aim to decrease energetic expenditure and attenuate physiology that depletes energy reserves such as CORT secretion, thus promoting energy conservation, which conserves (or even increases) body mass.…”
Section: Discussionmentioning
confidence: 99%
“…Males were used because a previous study demonstrated that they robustly adapt physiologically and behaviorally to variable amounts of food (Munn et al 2010). The animals were from a captive colony based at the University of Sydney, Sydney, New South Wales, Australia.…”
Section: Methodsmentioning
confidence: 99%
“…That function would be congruent with morning T c being determined by time of year, which also determines season. We do know that food deprivation leads to a lower rest-phase T c in some birds and mammals (Kanizsai et al, 2009;, and that the response is likely driven by proximate signals related to energy intake (Maloney et al, 1999;Munn et al, 2010). Offering sheep a diet containing only 70% of maintenance energy requirements, as opposed to 100% of maintenance energy requirements, also resulted in a significant decrease in the restphase T c (S.K.M., L.C.R.M., A.F.…”
Section: S K Maloney and Othersmentioning
confidence: 99%